2000
DOI: 10.1038/73804
|View full text |Cite
|
Sign up to set email alerts
|

Field tests on managing resistance to Bt-engineered plants

Abstract: Several important crops have been engineered to express toxins of Bacillus thuringiensis (Bt) for insect control. In 1999, US farmers planted nearly 8 million hectares (nearly 20 million acres) of transgenic Bt crops approved by the EPA. Bt-transgenic plants can greatly reduce the use of broader spectrum insecticides, but insect resistance may hinder this technology. Present resistance management strategies rely on a "refuge" composed of non-Bt plants to conserve susceptible alleles. We have used Bt-transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1
13

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(153 citation statements)
references
References 15 publications
2
137
1
13
Order By: Relevance
“…In principle, if resistance is recessive, the heterozygous progeny produced by such matings are killed by the Bt crop, and resistance evolution is greatly delayed. Results from models and short-term, small-scale experiments suggest that refuges can delay resistance substantially (3,(14)(15)(16), but long-term, largescale field tests of the refuge strategy have proved problematic.…”
Section: Bacillus Thuringiensis ͉ Resistance Management ͉ Transgenic mentioning
confidence: 99%
“…In principle, if resistance is recessive, the heterozygous progeny produced by such matings are killed by the Bt crop, and resistance evolution is greatly delayed. Results from models and short-term, small-scale experiments suggest that refuges can delay resistance substantially (3,(14)(15)(16), but long-term, largescale field tests of the refuge strategy have proved problematic.…”
Section: Bacillus Thuringiensis ͉ Resistance Management ͉ Transgenic mentioning
confidence: 99%
“…Together, the high dose and the refuge in this way almost equalize the fitnesses of the R and S alleles so that the R fraction increases only slowly. Mathematical modelling [3,34] has indicated the HDR idea as a good one, and experiments have confirmed that it can work in delaying resistance development [29].…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, a eficiência do controle químico tem sido reduzida em consequência da seleção de populações resistentes, sendo este fato constatado para alguns piretroides e organofosforados (Omoto et al, 2000;Diez-Rodrigues e Omoto, 2001;Cruz et al, 2006). Esta quebra de resistência por parte da lagarta-do-cartucho também pode vir a ocorrer no milho transgênico (Bt), o qual teve sua comercialização aprovada recentemente no Brasil, caso não seja realizado um manejo adequado da cultura (Shelton et al, 2000).…”
Section: Introductionunclassified